Blood Pressure and Lipid Profile in Automechanics in Relation to Lead Exposure - Obi-Ezeani, Chikaodili Nwando (Indian J Occup Environ Med, 2019)
CONTEXT: Elevated blood pressure and alterations in lipid and lipoproteins play a major role in the development and progression of cardiovascular diseases. AIM: This study is aimed at determining the blood pressure and lipid profile in automechanics. SETTINGS AND DESIGN: A total of 120 male subjects between 18 and 55 years of age comprised 60 automechanics and 60 age-matched occupationally unexposed control subjects in Emene, Enugu State, Nigeria. SUBJECTS AND METHODS: Four milliliters of fasting blood samples was collected from all subjects, 2 mL of blood was dispensed into K(2)-EDTA vacutainer tube for blood lead analysis, while the other 2 mL was dispensed into plain vacutainer tube, allowed to retract, centrifuged, and the serum used for serum lipid profile analysis. Blood pressure was measured using aneroid sphygmomanometer. STATISTICAL ANALYSIS: Statistical Package for Social Sciences (SPSS) version 21.0 was used for data analysis. RESULTS: Automechanics had significantly higher values of systolic and diastolic blood pressures compared with the controls. Serum levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), very low-density lipoprotein cholesterol (VLDL-C), and triglyceride (TG) were also significantly higher in the automechanics compared with the controls (P < 0.05); serum high-density lipoprotein cholesterol (HDL-C) level, however, did not differ significantly between the two groups (P > 0.05). Blood lead level showed a significant positive correlation (P < 0.05) with systolic and diastolic blood pressures, serum TC, LDL-C, VLDL-C, and TG, with no significant correlation with serum HDL-C (P > 0.05) in the automechanics and no correlation in the controls. CONCLUSION: The result of this study indicates that blood pressure is elevated and lipid profile altered in automechanics which suggests that these groups of workers are prone to increased risk of developing hypertension and cardiovascular disorders due to occupational exposure to lead.